CCNP security VPN 642-648 offical cert guide - Hooper, Howard (Indianapolis, IN : Cisco Press, 2012)
CCNP Security VPN 642-648 Official Cert Guide is a best of breed Cisco exam study guide that focuses specifically on the objectives for the CCNP Security VPN exam. Cisco Certified Internetwork Expert (CCIE) Howard Hooper shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics.
Includes index.
rpm 24/10/2017
Loans
Keywords: Computer networks--Security measures--Examinations; Electronic data processing personnel--Certification; Extranets (Computer networks); Computer networks; Telecommunications engineers--Certification